Cardiorespiratory effects of gap junction blockade in the locus coeruleus in unanesthetized adult rats - Patrone, Luis G. A. [UNESP]; Bicego, Kenia Cardoso [UNESP]; Hartzler, Lynn K.; Putnam, Robert W. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier B.V., 2014)
The locus coeruleus (LC) plays an important role in central chemoreception. In young rats (P9 or younger), 85% of LC neurons increase firing rate in response to hypercapnia vs. only about 45% of neurons from rats P10 or older. Carbenoxolone (CARB - gap junction blocker) does not affect the % of LC neurons responding in young rats but it decreases the % responding by half in older animals. We evaluated the participation of gap junctions in the CO2 ventilatory response in unanesthetized adult rats by bilaterally microinjecting CARB (300 mu M, 1 mM or 3 mM/100 nL), glycyrrhizic acid (GZA, CARB analog, 3 mM) or vehicle (aCSF - artificial cerebrospinal fluid) into the LC of Wistar rats. Bilateral gap junction blockade in LC neurons did not affect resting ventilation; however, the increase in ventilation produced by hypercapnia (7% CO2) was reduced by similar to 25% after CARB 1 mM or 3 mM injection (1939.7 +/- 104.8 mL kg(-1) min(-1) for the aCSF group and 1468.3 +/- 122.2 mL kg(-1) min(-1) for 1 mM CARB, P < 0.05; 1939.7 +/- 104.8 mL kg(-1) min(-1) for the aCSF group and 1540.9 +/- 68.4 mL kg(-1) min(-1) for the 3 mM CARB group, P < 0.05) due largely to a decrease in respiratory frequency. GZA injection or CARB injection outside the LC (peri-LC) had no effect on ventilation under any conditions. The results suggest that gap junctions in the LC modulate the hypercapnic ventilatory response of adult rats. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Carbenoxolone; Hypercapnia; A6; Ventilation; Electrical coupling